Kolaborasi penulis BACA dan Khizanah Al Hikmah Periode 2018-2020 - Rahayu, Rochani Nani; Sobari, Sobari Sobari (FPPTI Jawa Tengah, 2021)
ABSTRACT It is motivated by the desire to see the characteristics of journals, by comparing one journal with another that has the same subject. BACA and Khizanah Al Hikmah (KAH) both focus on the field of libraries, documentation with SINTA 2 accreditation. A bibliometric analysis of BACA and KAH is carried out with the aim of knowing: 1) Number of published articles; 2) The pattern of authorship of each journal; 3) Degree of collaboration; 4) The most prolific writer; 5) Gender of the author; 6) Writers from universities and other institutions; 7) Author's city; 9) Research topics based on the author's keywords. The data sources analyzed are accessed from: https://jurnalbaca.pdii.lipi.go.id/index.php/baca/issue/archive for the BACA journal and the website: http://journal.uin-alauddin.ac.id/ index.php/khizanah-al-hikmah for the journal KAH. The data recorded is the number of articles, name, gender, agency, city where the author works, and keywords. Furthermore, the data is processed using a frequency distribution in percentages, and presented in tabular form, for analysis and discussion, as well as conclusions. The result of the research is that the BACA journal published 60 articles, written by 56 men and 51 women. KAH published 57 articles written by 61 men and 60 women. Articles written by two authors, both on BACA (31.67%), and KAH (31.57%) are both the most common articles. The degree of collaboration between BACA authors was 0.73 and KAH 0.71, indicating that the authors collaborated more than individual authors. The University of Indonesia and UIN Allaudin are the universities that contribute the most to BACA and KAH. LIPI is the institution in first place for both BACA and KAH respectively 14 times (70%), and 11 times (61%). Jakarta is the largest city for both BACA and KAH. Most of the research topics are about academic library for BACA and Bibliometric for KAH. It is concluded that when viewed from the degree of collaboration, the two journals have a balanced number of collaborating authors.Keywords: Author collaboration;Journals;Degrre of collaboration